The Influence of Work Stress Levels and Supervisor Support on Employee Performance at Shopee Express Sribawono Branch, East Lampung - Fernanda Venturini; Syaiful Bakhri (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
The purpose of this study was to determine the effect of work stress and supervisor support on employee performance at Shopee Express Sribawono Branch. Employee performance served as the dependent variable, while work stress and supervisor support were the independent variables. This study employed a quantitative method with an associative approach. The research involved 100 employees, and the entire population was used as the sample through the total sampling technique. The data were processed and analyzed using SPSS software. Data were collected through the distribution of questionnaires using a Likert scale. The analyses included validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and coefficient of determination analysis. The results of the study indicate that work stress has a negative and significant effect on employee performance, with a significance value of 0.003 < 0.05, while supervisor support has a positive and significant effect on employee performance, with a significance value of 0.001 < 0.05. Furthermore, work stress and supervisor support simultaneously have a significant effect on employee performance, with a significance value of 0.000 < 0.05.